PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH PADA PEMBELAJARAN IPA MATERI TATA SURYA KELAS VI SDN KEBON BARU KOTA TANGERANG - Purwati, Purwati; Syachruroji, A.; Nulhakim, Lukman; Andriana, Encep (Journal of Professional Elementary Education, 2024)
This study aims to increase student interest in class VI by using interactive media based on Adobe Flash at SDN Kota Baru. The research method used by the author is the research and development method or Research and Development (R&D) which is the method used to produce certain products and test the effectiveness of these products. With seven stages: problem analysis, data collection, product design, product design validation, product revision, product testing, and final results. To prove the media from Adobe Flash interactive media, validation tests were carried out by media experts and material experts. After testing the product, the subject of this research is class VI SDN Kota Baru students. Based on the validation, it was stated that Adobe Flash interactive learning media was "very feasible" to be used. Validation carried out by media experts obtained a percentage value of 86% and material experts 94% who were in the "very feasible" category and the respondents given by students received 91.4 presentations. % that fall into the “very good” category. Based on the results of the study, it can be said that Adobe Flash interactive media is "very suitable for use in science learning".